Search for pair production of heavy particles decaying to a top quark and a gluon in the lepton+jets final state in proton–proton collisions at $$\sqrt{s}=13\,\text {Te}\hspace{-.08em}\text {V} $$ s = 13 Te V - CMS Collaboration (European Physical Journal C: Particles and Fields)
Abstract A search is presented for the pair production of new heavy resonances, each decaying into a top quark (t) or antiquark and a gluon (g). The analysis uses data recorded with the CMS detector from proton–proton collisions at a center-of-mass energy of 13 $$\,\text {Te}\hspace{-.08em}\text {V}$$ Te V at the LHC, corresponding to an integrated luminosity of 138 $$\,\text {fb}^{-1}$$ fb - 1 . Events with one muon or electron, multiple jets, and missing transverse momentum are selected. After using a deep neural network to enrich the data sample with signal-like events, distributions in the scalar sum of the transverse momenta of all reconstructed objects are analyzed in the search for a signal. No significant deviations from the standard model prediction are found. Upper limits at 95% confidence level are set on the product of cross section and branching fraction squared for the pair production of excited top quarks in the $$\text {t}^{*} → {\text {t}} {\text {g}} $$ t ∗ → tg decay channel. The upper limits range from 120 to 0.8 $$\,\text {fb}$$ fb for a $$\text {t}^{*} $$ t ∗ with spin-1/2 and from 15 to 1.0 $$\,\text {fb}$$ fb for a $$\text {t}^{*} $$ t ∗ with spin-3/2. These correspond to mass exclusion limits up to 1050 and 1700 $$\,\text {Ge}\hspace{-.08em}\text {V}$$ Ge V for spin-1/2 and spin-3/2 $$\text {t}^{*} $$ t ∗ particles, respectively. These are the most stringent limits to date on the existence of $$\text {t}^{*} → {\text {t}} {\text {g}} $$ t ∗ → tg resonances.